Achieving ambitions: roadmap to implementing nationally determined contributions for agriculture emission reduction in Vietnam - Nelson, Katherine; Sander, Björn Ole; Bui Tan Yen (Informa UK Limited, 2023)
The agriculture sector contributes significantly to national greenhouse gas emissions in developing countries. Rice is a major contributor to methane emissions in Asia and many countries have recognised the potential to reduce their emissions by including rice sector targets in their nationally determined contributions (NDCs) in the Paris Agreement. The NDC commitments are voluntary emission reduction efforts submitted by each country to curb global warming. This guide serves to bridge the gap in knowledge on developing and implementing action plans to achieve the ambitious targets to reduce emissions in rice. With a focus on Vietnam, this guide describes methods and tools for research organisations to support national governments to plan, finance, and implement mitigation actions in the rice sector.